1973
DOI: 10.1063/1.1679360
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency modes in molecular crystals. XIX. Methyl torsions and barriers to internal rotation of some three top molecules with C3 symmetry

Abstract: The low frequency infrared spectra of (CHa)aCOH, (CDa)sCOH, (CHa)aCSH, (CHa)aCNCO, (CHa)a-CNCS, (CHa)aCCHO, (CH.)aCNH2, (CHa)sCOCHa, and (CH.)aCODC. have been recorded for these molecules in both the gaseous and solid states. Harmonic barriers have been calculated for t-butyl methyl group rotation from frequencies measured for the compounds in their solid state. The values are 4. 13, 4.52,4.41, 4.67, 4.86, 3.96, 4.28, 4.71, and 4.55 kcal/mole, respectively. Estimates of the periodic barriers to rotation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A number of infrared and Raman studies on monosubstituted amides in both liquid and solid state suggested the presence of in-phase and outof phase CCH 3 and NCH 3 methyl torsions in the 6900-9000 GHz frequency range. [58][59][60][61] Fig. 4 VDOS profiles at room temperature obtained from NS experiments (black diamonds) and MD simulations (pink line) on dry NALMA.…”
Section: Resultsmentioning
confidence: 99%
“…A number of infrared and Raman studies on monosubstituted amides in both liquid and solid state suggested the presence of in-phase and outof phase CCH 3 and NCH 3 methyl torsions in the 6900-9000 GHz frequency range. [58][59][60][61] Fig. 4 VDOS profiles at room temperature obtained from NS experiments (black diamonds) and MD simulations (pink line) on dry NALMA.…”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, the C02 that forms inside the crystal has been observed to escape preferentially from the (102) face. In the loss of HC1 by p-aminosalicylic acid hydrochloride,82 the escape of HC1 was also found to be dependent on the crystal habit of the sample, and in the reaction between gaseous Cl2 and solid 2-methylphenol,83 6or 4-chlorinated derivatives were obtained depending on how the crystal samples had been cut.…”
Section: Some Examplesmentioning
confidence: 97%
“…Calculations of rotation barrier about the central C-O bond in C3COC (Figure 1) yields a 3-fold symmetrical potential where the maxima occur when a methyl group eclipses one of the three -CH 3 groups on the quaternary C atom at a barrier of 2.9 kcal/mol. Durig et al 40 reported the barrier of 3.57 kcal/mol from the analysis of far-infrared spectra in the gas phase. This 0.7 kcal/mol difference for the barrier results in an error of 0.3 and 0.03 cal/(mol K) at 298 K for the entropy and heat capacity contribution from internal rotation, respectively.…”
Section: Entropies (S°(t)'s) and Heat Capacities (C P (T)'s) (50 E T/...mentioning
confidence: 99%